Evaluation of Drug-induced Liver Injury and its Relationship with NAT2 Gene Polymorphisms in Tuberculosis Patients - Farhang Babamahmoodi; Samaneh Kamalabadi Farahani; Dariush Ramezani; Nematollah Ahangar (Journal of Mazandaran University of Medical Sciences, 2017)
Background and purpose: The main purpose of this study was determination of different genotypes and phenotypes of N-acetyltransferase 2 gene and its relationship with drug-induced liver injury among patients in Mazandaran province, Iran, which was done for the first time. Materials and methods: A total of 65 newly diagnosed unrelated pulmonary tuberculosis patients (47 men, 18 women) was enrolled in the study. A combination of polymerase chain reaction -restriction fragment length polymorphism method was used to investigate different allels of N-acetyltransferase-2. The patients were followed for occurrence of antituberculosis induced hepatotoxicity during the course of treatment. Relationship between N-acetyltransferase-2 phenotypes and antituberculosis induced hepatotoxicity was evaluated. Results: Frequency of slow, intermediate and fast acetylator genotypes in patients were 34%, 60% and 6%, respectively. Hepatotoxicity was diagnosed in 13.64% of slow acetylators, in 2.56% of intermediate acetylators and interestingly in none of the fast acetylators. The Chi-Square Test showed no significant difference between different acetylation phenotypes and risk of hepatotoxicity (P = 0.1086). Conclusion: These results could improve treatment profile, prevent from drug-related adverse effects such as hepatotoxicty and lead to better outcomes in tuberculosis patients.